Depth Modulation of the Attentional Repulsion Effect. (December 2013) - Chien, Sung-En; Watanabe, Katsumi
Shifts of attention can cause mislocalisation of visual objects. A brief cue that attracts attention can cause a shift in the perceived location of a subsequently presented visual object—specifically, moving it away from the focus of attention (attentional repulsion). In the present study we investigated whether depth would influence the magnitude of attentional repulsion by presenting peripheral visual cues in different depth planes from the target or fixation. In experiment 1 the results showed that the magnitude of the attentional repulsion was larger when the cue was presented at the depth plane farther away from the target and fixation. In experiment 2 we presented the fixation point in the same depth plane as the nearest cues and found larger repulsion effects when the cues were presented in depth planes farther away from the fixation. In experiment 3 no depth modulation was observed when the fixation was presented in the same depth plane with the farthest cues. Taken together, when the cues were presented in the depth plane farther away from the fixation, the magnitude of the attentional repulsion effect increased. It is speculated that the residual coarser spatial representation in the space farther from the fixation plane or the enhanced attentional process for the space closer than the fixation may be responsible for the larger attentional repulsion effect.